Double seal in corn silage in confined cattle production - Neumann, Mikael; Leão, Guilherme Fernando Mattos; Santos, Leslei Caroline dos; Marafon, Fabiano; Askel, Eloize Jaqueline (Revista de Ciências Agroveterinárias, 2018)
System production success of beef cattle is based on forage quality, since it impacts in greater or lesser way the performance and, consequently, on the economic return. In this context, the objective of the present study was to evaluate productive performance, ingestive behavior and carcass characteristics and the noncarcass components of confined steers receiving corn silage submitted to two types of sealing strategy: VC - corn silage preserved with polyethylene Double-sided with a thickness of 110 μm (conventional sealing) and DV - preserved corn silage with double-sided polyethylene with a thickness of 110 μm superimposed on another translucent polyethylene with a thickness of 110 μm (double sealing). The determination of forage concentrate ratio revealed that the double-sealed system favored the lower participation of the concentrated fraction in this treatment (45.4 vs 48.3%), with a consequent increase in daily dry matter intake (10,04 vs 9.28 kg), and in relation to live weight (2.30 vs 2.21%), and increase in average daily gain (1.810 vs 1.565 kg). As for behavioral evaluation, animals receiving double-sealing system silage spent less time feeding (3.52 vs 4.60 hours day-1) and rumination (7.07 vs 7.94 hours day-1), and more leisure time (13.22 vs 11.28 hours-1). Regarding the carcass characteristics and non-carcass components, there was no statistical difference between the treatments. Steers receiving silage with a double-sealed system presented better productive performance.